STUDENTS’ CONCEPTUAL UNDERSTANDING OF SYSTEMS OF LINEAR EQUATIONS IN TWO VARIABLES: A DESCRIPTIVE QUANTITATIVE STUDY AT THE JUNIOR HIGH SCHOOL LEVEL - Alfiyah, Khomsyatun; Arisa, Nadia (Perpendicular : Journal of Mathematics Education and Learning, 2025)
This study aimed to analyze junior high school students’ conceptual understanding of Systems of Linear Equations in Two Variables (SLETV) based on conceptual understanding indicators at SMP Fitra Abdi Palembang. Conceptual understanding is a fundamental ability in mathematics learning; however, many students experience difficulties in applying mathematical concepts to contextual problems. This study employed a descriptive quantitative method involving 31 ninth-grade students selected through random sampling. Data were collected using an essay test consisting of seven items aligned with conceptual understanding indicators. The results showed that students’ overall conceptual understanding was categorized as high, with an average score of 60.50. Students demonstrated very high achievement in recognizing and restating concepts (92.47%) and presenting concepts in various representations (83.87%). However, the lowest achievement was found in applying concepts or algorithms to problem-solving (26.89%), indicating difficulties in connecting abstract concepts with real-life situations. These findings suggest that teachers should emphasize learning strategies that promote conceptual application, such as Problem-Based Learning or contextual approaches, to improve students’ ability to apply mathematical concepts meaningfully. This study contributes to mathematics education by providing a detailed profile of students’ conceptual understanding indicators that can serve as a reference for instructional improvement.